Alterações torácicas musculoesqueléticas no primeiro ano de vida em crianças nascidas prematuras: fatores associados e importância da fotogrametria para o seu diagnóstico - Davidson, Josy [UNIFESP] (2009)
Objective: To determine the frequency and factors associated with thoracic musculoskeletal alterations in infants born premature and to analyze the accuracy and the reproducibility of photogrammetry to detect these alterations. Methods: Cross sectional study with infants in the first year of life, born from February/2007 to December/2008, with gestational age <37 weeks, birth weight <2000g and followed at the Premature Clinic of the Federal University of São Paulo. Major malformation, intraventricular hemorrhage grade III/IV and/or periventricular leucomalacia were excluded. Physical exam was used as a reference standard to determine the frequency and factors associated with thoracic alterations and for accuracy analysis, by ROC curve. Photographs were analyzed by a computer program to detect shoulder elevation and thoracic retraction by the measurement of manubrium/acromion process/trapezius angle and the greatest thoracic retraction depth. The study was approved by the Ethical Committee of the Institution and parents/guardians signed terms of informed consent. Results: Of 121 studied infants (gestational age: 31.1+2.8 weeks, birth weight: 1400+338g), 81 (66.9%) presented thoracic alterations. By logistic regression, factors associated with thoracic alterations were: days of corrected age (OR=1.018, CI95%: 1.004-1.019) and days on oxygen therapy (OR=1.096, CI 95%: 1.031-1.164). Compared to physical exam, the manubrium/acromion process/trapezius angle presented: accuracy: 0.793, sensitivity: 71.4%, specificity: 78.4%, intraclass and interclass correlation coefficient (ICC): 0.922 and 0.947. The greatest thoracic retraction depth showed: accuracy: 0.895, sensitivity: 96.6%, specificity: 75.9%, (ICC): 0.841 and 0.838. Conclusions: The frequency of thoracic alterations was high and associated with higher corrected age and longer oxygen therapy. The photogrammetry provided an objective, accurate and reliable test to detect thoracic alterations in preterm infants.